Acromioclavicular joint arthritis as the first manifestation of Austrian syndrome. Issue 1 (January 2020) - Miyaue, Noriyuki; Yamanishi, Yuki; Tada, Satoshi; Ando, Rina; Yabe, Hayato; Nagai, Masahiro
Abstract: Austrian syndrome is a rare condition caused by invasive Streptococcus pneumoniae, comprising a triad of pneumococcal meningitis, endocarditis, and pneumonia. Herein, we report a 59-year-old male patient who presented with fever and tenderness of the right shoulder. Although the initial diagnosis was acromioclavicular joint septic arthritis, the present case showed a reduced level of consciousness, pulmonary infiltrates, cerebral infarcts, and destruction of the mitral valve. This case suggests that acromioclavicular joint arthritis could be an initial presentation of pneumococcal infection inclusive of Austrian syndrome, especially in patients with some risk factors of invasive pneumococcal infections, such as chronic alcoholism.